Microbial Contamination in Some Commercial Biscuits in Baghdad City (Baghdad Science Journal, 2010)
This study has been conducted to know the level of microbial ( bacteria and fungi) contamination in 5 types of biscuits from local markets of Baghdad city. Fifty samples (ten sample for each kind of biscuit) were studed,Two are local,others are Iranian,Turkish,and Holandies. The following results have been achieved :1. The highest number of bacteria was 21.6×103 cell/g in Iranian biscuit while the lowest number was 14.3× 103 cell/g in local biscuit No.1 . The highest number of fungi was 16×103 colony/g and the lowest number was 5.3×103 colony/g in the Iranian and the local biscuit No.1,respectively.2. Staphylococcus aureus was the major bacteria appeared at highest level of 100% in Turkish biscuit. The lowest percentage was found in Hollandian biscuit with 37.28%. Bacillus cereus was the major bacteria with a percentage of 100% in local biscuit No.2 where as the lowest was in local biscuit No,1with a percentage of 20.93%, while it was not existed in Turkish biscuit. Esherichia coli was found in Hollandian biscuit at highest rate of 38.98% , the lowest value was appeared in Iranian biscuit with 28.16% while it was not exited in local biscuit No.1,2 and Turkish biscuit.3. Aspergillus niger appeared at highest level of 66.66% in Hollandian biscuit, while was the lowest 37.73% in local biscuit No.1 and not existed in local biscuit No.2, The highest value of A.flavus was 69.76% in local biscuit No.2 and the lowest value in Hollandian biscuit in percentage 8.33%. It has not appeared in Iranian and Turkish biscuit. The A. terreus appeared at highest rate in Turkish biscuit with 33.33% , the lowest value was in local biscuit No.2 at 11.62% and was not appeared in Hollandian biscuit.The Penicillium spp. Was found at highest rate 25% in Hollandian biscuit , the lowest value of 9.52% was appeared in Turkish biscuit.